LAYOUT PLANNING FLOOR PRODUCTION BREAD FACTORY USING SYSTEMATIC LAYOUT PLANNING METHODS - Cipto Ramdhani Yusuf (Journal of Industrial Engineering and Halal Industries, 2020)
Tight competition in the food industry especially bread does not shrink the sales of bread produced by CV. Anni Bakery, but there are some problems that arise at this time, the limited production floor which is increasingly narrow due to increased production without adjusting existing capacity and the irregular placement of production floor facilities. The background is used as a reference for the company to create a new factory. The purpose of this study is to propose the layout of production floor facilities with the right facility layout so that the cost of transferring materials is small. The systematic layout planning (SLP) approach was used. The result performance of the 1st proposal layout obtained material handling distance of 405 meters while in the 2nd proposal layout the material handling distance becomes 386 meters. The cost of moving the proposed material to 1 obtained a total cost of 22,644,300 rupiah per month, while in the second material transfer fee the total cost of 21,993,825 rupiah per month. Based on the alternative initial layout and the proposed layout, the most suitable layout is the second proposal layout.. So this facility layout plan is feasible for new factory to create.